New candidate vaccines against blood-stage plasmodium falciparum malaria: prime-boost immunization regimens incorporating human and simian adenoviral vectors and poxviral vectors expressing an optimized antigen based on merozoite surface protein 1 - Goodman, Anna L.; Epp, Christian; Moss, D.; Holder, A. A.; Wilson, J. M.; Gao, G. P.; Long, C. A.; Remarque, E. J.; Thomas, A. W.; Ammendola, V.; Colloca, S.; Dicks, M. D. J.; et al. (Infection and immunity, 2010)
Although merozoite surface protein 1 (MSP-1) is a leading candidate vaccine antigen for blood-stage malaria, its efficacy in clinical trials has been limited in part by antigenic polymorphism and potentially by the inability of protein-in-adjuvant vaccines to induce strong cellular immunity. Here we report the design of novel vectored Plasmodium falciparum vaccines capable of overcoming such limitations. We optimized an antigenic insert comprising the four conserved blocks of MSP-1 fused to tandemly arranged sequences that represent both allelic forms of the dimorphic 42-kDa C-terminal region. Inserts were expressed by adenoviral and poxviral vectors and employed in heterologous prime-boost regimens. Simian adenoviral vectors were used in an effort to circumvent preexisting immunity to human adenoviruses. In preclinical studies these vaccines induced potent cellular immune responses and high-titer antibodies directed against MSP-1. The antibodies induced were found to have growth-inhibitory activity against dimorphic allelic families of P. falciparum. These vectored vaccines should allow assessment in humans of the safety and efficacy of inducing strong cellular as well as cross-strain humoral immunity to P. falciparum MSP-1.
Gesehen am 26.04.2023